Effect of agrotechnical factors on the yield of the Grolim asparagus (Asparagus officinalis L.) hybrid on acidic sandy soil - Erdős, Zsuzsa (Acta Agraria Debreceniensis, 2018)
Research of blanched asparagus has begun at the University of Debrecen Institutes for Agricultural Research and Educational Farm Research Institutes of Nyíregyháza in 2011. Establishment of the plantation took place in May 2011. The Grolim hybrid was used in the trial, 16 medium plot trial area has been formed under field conditions, with four repetitions and 36 m2 plot size. In the course of our studies, the effect of different nutriment supply methods (untreated, manure, sheep manure compost, fertilizer) has been analysed on the spear yield of the Grolim asparagus hybrid between 2013 and 2017.In our studies, the beginning of vegetative growth has been recorded upon the constant presence of 10 °C of average soil temperature in the case of the Grolim asparagus hybrid. The beginning and length of spear harvesting are both influenced by the time and dynamics of initial development in spring. During the analysed period, the dates of spear harvesting were various, the earliest being on 23rd March, 2014 and the latest on 23rd April, 2015; the rest of the three years have been varied within this one month interval. The total of heat units required for the vegetative development of spears has been determined; it provides important information for cultivation practice.Spear yields turned out to be hectic during the analysed period. In 2013 and 2014, yields have surpassed the amount of 50 kg/harvest period/plot in the case of every treatment version. However, in 2015 a significantly lower specific yield has been recorded due to the unfavourable weather conditions in spring; a yield decline of nearly 50% was recorded in the case of the control treatment compared to the previous years. Yield was also lower in the rest of the fertilization treatments compared to 2014; however, in these cases, the degree of yield decrease was around 5–10%, which suggests the yield stabilising effect of fertilization. In 2016, a slight yield increase was measured in comparison with the base year. In 2017, there was a decline of yield in the control treatment; however, the different fertilization treatments resulted in yield increase as compared to previous years.On the basis of our studies, it is clear that the best yield results have been provided by the artificial fertilization treatment in all of the five analysed years. It was followed by the sheep manure compost and manure treatments in terms of their effect on spear yield. During the three harvesting periods, the lowest yield on acidic sandy soil was recorded in the case of the control treatment. The most remarkable effect of nutriment treatments has been realised in terms of the decreased deviation of yield results, which perfectly represents the yield stabilising effect of nutriment supply in the case of perennial crops – asparagus – as well, even on a poor nutriment supply characteristic sandy soil.